2021
DOI: 10.1007/s13258-021-01175-z
|View full text |Cite
|
Sign up to set email alerts
|

YTHDF1 promotes the proliferation, migration, and invasion of prostate cancer cells by regulating TRIM44

Abstract: Background Prostate cancer (PCa) is one of the most common malignancies in men. YTHDF1 may play an important role in promoting PCa progression, but there is no reports to date on YTHDF1 function in PCa. Objective This study explored whether YTHDF1 could regulate TRIM44 in PCa cells. Methods By querying the TCGA database, we evaluated YTHDF1 expression in PCa, the OS and DFS of YTHDF1, and the correlation between YTH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Overexpression of YTHN6-methyladenosine RNA binding protein 1 (YTHDF1), an N6-methyladenosine modification (m6A) reader, rescues the DSB DNA damage response 49 . A previous study demonstrated that TRIM44 is transcriptionally upregulated by YTHDF1 50 . In the DDR, whether the DSB-induced abundance of TRIM44 is dependent on YTHFF or other m6A enzymes requires further investigation.…”
Section: Discussionmentioning
confidence: 93%
“…Overexpression of YTHN6-methyladenosine RNA binding protein 1 (YTHDF1), an N6-methyladenosine modification (m6A) reader, rescues the DSB DNA damage response 49 . A previous study demonstrated that TRIM44 is transcriptionally upregulated by YTHDF1 50 . In the DDR, whether the DSB-induced abundance of TRIM44 is dependent on YTHFF or other m6A enzymes requires further investigation.…”
Section: Discussionmentioning
confidence: 93%
“…The YTHDF family genes ( YTHDF1 , YTHDF2 , and YTHDF3 ) can recognize bases undergoing m6A methylation, as well as bases participating in downstream translation, mRNA degradation, and mRNA exit rate acceleration [ 60 ]. Previous studies have demonstrated that PC samples expressed higher levels of YTHDF1 and YTHDF2 mRNA compared to healthy tissue [ 61 , 62 ]. Upregulation of YTHDF1 and YTHDF2 promotes PC cell proliferation, invasion, and migration [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that PC samples expressed higher levels of YTHDF1 and YTHDF2 mRNA compared to healthy tissue [ 61 , 62 ]. Upregulation of YTHDF1 and YTHDF2 promotes PC cell proliferation, invasion, and migration [ 61 , 62 ]. In particular, YTHDF2 modulated PC phenotypes by regulating the expression of its significantly positively correlated gene, tripartite motif-containing 44 ( TRIM44 ) [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Prostate cancer TRIM44 Upregulated YTHDF1 promoted PCa cell proliferation, migration, and invasion by regulating TRIM44. Moreover, the prognosis of patients with PCa with high YTHDF1 was relatively poor [ 56 ]. Esophageal carcinoma / Upregulated Expression of YTHDF1 was associated with multiple clinical features in ESCA patients and involved in multiple ceRNA network [ 59 ].…”
Section: The Molecular Mechanism Of Ythdf1 In Cancersmentioning
confidence: 99%